No significant gender differences in driving-related skills following alcohol mixed with energy drinks during an experimental binge-drinking episode - Hladun, Olga; Papaseit, Esther; Poyatos, Lourdes; Martín, Soraya; Pérez-Acevedo, Ana Pilar; Barriocanal, Ana Maria; Bustos-Cardona, Tatiana; Malumbres, Susana; De La Torre, Rafael; Langohr, Klaus; Farré, Magí; Pérez-Mañá, Clara (Frontiers in Pharmacology, 2025)
IntroductionConsumption of alcohol mixed with energy drinks (AmEDs) is trendy among young people. It has been related to risk-taking behaviors like binge drinking and driving under the influence of alcohol. Previous data suggest that women are more sensitive to alcohol-induced impairment. The aim of the study was to assess whether women experience greater acute effects (on driving-related skills and subjective and physiological responses) after the controlled administration of alcohol and energy drinks in an experimental binge-drinking episode.MethodsA randomized, crossover, double-blind clinical trial was conducted with 28 healthy volunteers (14 men and 14 women) across four treatment conditions, namely, alcohol + energy drink (A/ED), alcohol + placebo of ED (A), placebo of alcohol + ED (ED), and both placebos (P). Men received 70 g of alcohol and women received 55 g, combined with 750 mL and 589 mL of ED, respectively; these were administered over 80 min, mimicking a binge-drinking episode. Driving-related skills (measured by a tracking test and the psychomotor vigilance task), subjective effects (using the visual analog scales (VASs, Biphasic Alcohol Effects Scale (BAES), and Addiction Research Center Inventory (ARCI)), vital signs, and alcohol and caffeine concentrations were measured over an 8-h period.ResultsPeak alcohol concentrations in breath air were 0.46 mg/L in both genders, despite the alcohol dose being 21% lower in women. Similar peak blood caffeine concentrations were observed in men and women (4,500 ng/mL vs. 4,635 ng/mL with A/ED, higher than those with ED). Women reported greater drunkenness (effect size: 45 mm; 95% CI: 5–85 mm) and more alcohol-induced sedation than men (ARCI sedative subscale effect size: 12; 95% CI: 2–22), but no significant gender differences were found in driving-related skills. AmEDs slightly reduced alcohol's effects on most subjective and psychomotor outcomes, but ED did not entirely offset alcohol's effects, and no interaction between the two beverages was found for either gender.ConclusionAfter a binge-drinking episode, women reported greater drunkenness and more sedation than men. Our results support that women are more sensitive to several subjective effects of alcohol, but further studies should be conducted to better elucidate gender differences in the effects of AmEDs on driving performance. ClinicalTrials.gov NCT04616859.